1999
DOI: 10.1038/13484
|View full text |Cite
|
Sign up to set email alerts
|

A universal influenza A vaccine based on the extracellular domain of the M2 protein

Abstract: The antigenic variation of influenza virus represents a major health problem. However, the extracellular domain of the minor, virus-coded M2 protein is nearly invariant in all influenza A strains. We genetically fused this M2 domain to the hepatitis B virus core (HBc) protein to create fusion gene coding for M2HBc; this gene was efficiently expressed in Escherichia coli. Intraperitoneal or intranasal administration of purified M2HBc particles to mice provided 90-100% protection against a lethal virus challenge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
575
0
8

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 696 publications
(600 citation statements)
references
References 42 publications
17
575
0
8
Order By: Relevance
“…Regarding immune mechanisms of protection by A/NP+A/M DNA vaccination, candidates include CTL specific for NP (17) and antibodies to the N-terminal portion of M2 (18). Containing an infection with the kinetics of HK/483 may be difficult because it reaches near peak titers in as little as 24 hours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding immune mechanisms of protection by A/NP+A/M DNA vaccination, candidates include CTL specific for NP (17) and antibodies to the N-terminal portion of M2 (18). Containing an infection with the kinetics of HK/483 may be difficult because it reaches near peak titers in as little as 24 hours.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have demonstrated potent and long-lasting heterosubtypic immunity, that is, exposure to a virus of one subtype protects against challenge infection with another subtype (10–15). The mechanisms of heterosubtypic immunity are not completely understood but likely include both T-cell immunity, in particular CD8+ cytotoxic T-lymphocytes (CTL) (16,17) and CD4+ T cells (13), as well as antibodies to conserved epitopes (18). Heterosubtypic immunity has been reported in humans (19, 20), but its effectiveness and duration are unknown.…”
mentioning
confidence: 99%
“…Although the recently emerged pandemic influenza A California strain exhibits four mutations within this domain, the C-terminal 11 amino acid have been completely conserved. In addition, M2e-specific antibodies protect mice [15][16][17][18][19][20], ferrets,…”
Section: Introductionmentioning
confidence: 99%
“…Although the recently emerged pandemic influenza A California strain exhibits four mutations within this domain, the C-terminal 11 amino acid have been completely conserved. In addition, M2e-specific antibodies protect mice [15][16][17][18][19][20], ferrets, and monkeys [21,22] from infection with various different flu strains. Hence, M2e-based vaccines may be promising candidates for pandemics since they could be stockpiled in large amounts prior to the event.…”
Section: Introductionmentioning
confidence: 99%
“…However, as the M2 is expressed on the surface of infected cells, it is a relevant target provided such an immune response could be initiated in the first place. To date several promising preclinical studies have been completed demonstrating a heterosubtypic response 38 , 39 . A clinical trial in humans is now underway (Table 1).…”
Section: Pandemic Vaccinesmentioning
confidence: 99%